The development of a prototype carbon fibre reinforced plastic (CFRP) rebar/strand by using hand lay-up moulding technique for its mechanical properties study [microfilm] - 454475 Hasnul Hadi Hashim; Hasnul Hadi Hashim (Skudai : Universiti Teknologi Malaysia, 1999)
Thesis (Postgraduate Diploma (Civil Engineering)) - Universiti Teknologi Malaysia, 1999